(untitled) (Bangladesh Journal of Pharmacology, 2013)
Bombax ceiba bark extract was evaluated for its hypoglycemic and hypolipide-mic potential through normal and streptozotocin-induced diabetic rats administered with graded oral doses (200, 400, 600 mg/kg/day) for 21 days. The results showed that a dose of 600 mg/kg of B. ceiba extract is the most effective to cause significant (p<0.001) hypoglycemic and/or hypolipidemic effects on streptozotocin-induced diabetic rats. This dose also significantly (p<0.001) lowered the total cholesterol and triglyceride level in severely diabetic rats. Phytochemical and GC-MS studies confirmed the presence of the triterpenoid compounds in the extract, which may account for its significant hypoglycemic activity. The present study thus provides a scientific rationale for the traditional use of this plant in the management diabetes.